Pengaruh Knowledge Management, Pelatihan dan Kepuasan Kerja terhadap Produktivitas Kerja pada UMKM Kampung Batik Giriloyo Kabupaten Bantul - Trianawati, Feri; Hadi, Syamsu; Septyarini, Epsilandri (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to determine the influence of knowledge management, training and job satisfaction on work productivity in MSMEs in Batik Giriloyo Village, Bantul Regency, both partially and simultaneously. In this research, researchers used quantitative research methods. The number of batik making samples that will be taken from the UMKM Batik Village Giriloyo, Bantul Regency is 60 respondents. The data in this study was collected using a questionnaire. Data analysis using Multiple Linear Regression. The research results show that knowledge management has a negative and insignificant effect on work productivity. Training has a positive and significant effect on work productivity. Job satisfaction has a positive and significant effect on work productivity. Knowledge Management, training, and job satisfaction have a positive and simultaneous effect on work productivity.